Abrasive blasting of lithium metal surfaces yields clean and 3D structured lithium metal anodes with superior properties - Wolf, Andreas; Lorrmann, Henning; Flegler, Andreas; Wolf, Andreas J.; Guerﬁ, Abdelbast; Mandel, Karl; Giffin, Guinevere A. (Energy Technology, 2021)
Avoiding harmful passivation of the lithium metal surface during its implementation as an anode material is a challenge to its use in rechargeable lithium metal batteries. It is critical to control the chemical composition and the morphology of the native passivation layer and to avoid contamination by lubricants or other substances involved in the processing. Herein, abrasive blasting is used as a physical method to achieve clean and 3D-structured lithium metal electrodes. The careful choice of the abrasive agent and the blasting parameters results in well-controlled surface properties. The blasted lithium electrodes exhibit significantly lower overvoltages with values as low as 10 mV at 0.1 mA cm−2. Electrochemical impedance spectroscopy shows that blasted lithium has interface resistances that are up to five times smaller than those of untreated lithium. The effectiveness of blasting as a cleaning method is clear even in the case of thicker and highly resistive passivation layers occurring after exposure to ambient air.